Decarbonization of Power Markets under Stability and Fairness: Do They Influence Efficiency? - Christoph Weissbart (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Market integration is seen as a complementary measure to decarbonize energy markets. In the context of power markets, this translates into regions that coordinate to maximize welfare in the power market with respect to a climate target. Yet, the maximization of overall welfare through cooperation leads to redistribution and can result in the reduction of a region's welfare compared to the case without cooperation. This paper assesses why cooperation in the European power market is not stable from the perspective of single regions and identifies cost allocations that increase fairness. In a first step, the EU-REGEN model is applied to find the future equilibrium outcome of the European power market under a cooperative, subadditive cost-sharing game. Secondly, resulting cost allocations are analyzed by means of cooperative game theory concepts. Results show that the value of cooperation is a exteuro 69 billion reduction in discounted system cost and rational behavior of regions can maintain at most 16 % of this reduction. The evaluation of alternative cost allocations reveals the trade-off between accounting for robustness against cost changes and individual rationality. Moreover, the cost-efficient decarbonization path of the European power sector under the grand coalition is characterized by the interplay between wind power, gas power, and biomass with geologic storage of CO2. Last, with singleton coalitions only, the market outcome shifts to a higher contribution from nuclear power.
Keywords: C60; C70; L90; Q40; 330; decision under risk; time constraints; opportunity costs; rational behavior; lab experiment; structural estimation; drift diffusion model